Factors Associated with Psychological Disorders in Health Workers Specializing in Handling Covid-19 in Several Padang City Government Hospitals - Nisura, Egi; Yetti, Husna; Kasra, Kamal (GoAcademica Research & Publishing, 2024)
The 2019 coronavirus disease can be spread quickly and easily, making it a potential pandemic threat. As the number of confirmed cases rises, the mental load of healthcare providers will increase, causing them to feel stressed, anxious, and negatively impacted emotionally. The primary objective of this study is to identify risk factors for mental illness among healthcare workers in Padang, Indonesia, who deal with the Covid-19 virus. The research used an explanatory sequential mixed methods design, beginning with a cross-sectional study to provide a quantitative foundation, then progressing to a more in-depth explanation using qualitative methods. There were a total of 1218 participants in this analysis. Using questionnaires and in-person interviews, we gathered information to analyze using the chi-square with 95% confidence interval and the anova test. 5.2% of healthcare workers handling Covid-19 reported moderate depression, 8.7% reported moderate anxiety, there was no correlation between occupation, interaction, residence, or average length of employment or salary, and there was no difference between the two.